Evaluating Fundal Dominant Contractions on Spatiotemporal Electrohysterography as a Marker for Effective Labor Contractions - Edwards, Rodney K.; Euliano, Neil R.; Singh, Savyasachi; LeDuke, Rachel C.; Andrews, William W.; Jauk, Victoria; Subramaniam, Akila; Szychowski, Jeff M. (American Journal of Perinatology, 2019)
Objective To evaluate if fundal (F) dominance of the electrohysterogram is associated with vaginal delivery and lack of F dominance is associated with cesarean for labor dystocia.Study Design We conducted a prospective cohort study of nulliparous women in spontaneous labor at ≥36 weeks. Clinicians were blinded to electrohysterography data which were in addition to standard cardiotocography. All contractions in the hour preceding diagnosis of complete cervical dilation (for women delivering vaginally) or the hour preceding the decision for cesarean were analyzed.Results Of 224 patients, 167 had evaluable data. The proportion of F dominant contractions was not different for women undergoing cesarean for labor dystocia (n = 11) compared with all others (n = 156)—88.7 ± 10.2 versus 86.0 ± 11.4%; p = 0.44. Results were similar when comparing the cesarean for labor dystocia group to those undergoing cesarean for other indications (n = 10) and vaginal deliveries (n = 146)—88.7 ± 10.2 versus 86.5 ± 10.0 versus 85.9 ± 11.5%; p = 0.74.Conclusion We were unable to confirm our earlier finding that F dominance of the electrohysterogram is associated with vaginal delivery and lack of F dominance is associated with cesarean for dystocia.
Keywords: labor; labor dystocia; electrohysterography; cesarean delivery; uterine contraction; monitoring